2017
DOI: 10.1039/c7md00125h
|View full text |Cite
|
Sign up to set email alerts
|

An insight into tetrahydro-β-carboline–tetrazole hybrids: synthesis and bioevaluation as potent antileishmanial agents

Abstract: A series of 2,3,4,9-tetrahydro-β-carboline tetrazole derivatives () have been synthesized utilizing the Ugi multicomponent reaction and were identified as potential antileishmanial chemotypes. Most of the screened derivatives exhibited significant activity against the promastigote (IC from 0.59 ± 0.35 to 31 ± 1.27 μM) and intracellular amastigote forms (IC from 1.57 ± 0.12 to 17.6 ± 0.2 μM) of , and their activity is comparable with standard drugs miltefosine and sodium stibogluconate. The most active compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The authors took the gathered data for the whole compound series to build comparative molecular field analysis (CoMFA) models that suggested that several modifications can enhance the anti-leishmanial potential of α–aminophosphonates. Similar approaches identified 1,2,3-triazole and thiosemicarbazone hybrids and tetrahydro-β carboline derivatives as candidate anti-leishmanial drugs [ 98 ]. Novel quinazoline and arylimidamide derivatives have been identified using 3D QSAR-based analysis against T. cruzi [ 99 ].…”
Section: Cheminformatics In Drug Discoverymentioning
confidence: 99%
“…The authors took the gathered data for the whole compound series to build comparative molecular field analysis (CoMFA) models that suggested that several modifications can enhance the anti-leishmanial potential of α–aminophosphonates. Similar approaches identified 1,2,3-triazole and thiosemicarbazone hybrids and tetrahydro-β carboline derivatives as candidate anti-leishmanial drugs [ 98 ]. Novel quinazoline and arylimidamide derivatives have been identified using 3D QSAR-based analysis against T. cruzi [ 99 ].…”
Section: Cheminformatics In Drug Discoverymentioning
confidence: 99%
“…Further, in-vivo evaluation of the compound 48 against L. donovani golden hamster model at a dose of 50 mg kg −1 (i.p for five days) showed 75.04 ± 7.28% inhibition of splenic parasite burden. Pharmacokinetics of compound 145 was also studied in the golden Syrian hamster followed with a 50 mg kg −1 oral dose, the compound 145 was detected in hamster serum for up to 24 h. It showed a large volume of distribution (651.8 L kg −1 ), high clearance (43.2 L h −1 kg −1 ), and long mean residence time (10 h) ( Purohit et al., 2017 ) (see Figure 16 ).
Figure 16 Structure of compound 145 .
…”
Section: Biological Activitymentioning
confidence: 99%
“…A key feature of the tetrazole ring is its bioisosteric character with the carboxylic acid and amide functional groups, which has been considered of interest for medicinal chemistry applications [78]. In recent years, the preparation of hybrid heterocyclic scaffolds including the tetrazole ring (either fused or linked to other heterocycles) has rendered potent bioactive compounds [913], which confirms the prospect of the tetrazole hybridization strategy in drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most versatile methods for obtaining tetrazoles are the Ugi-azide four-component reaction (Ugi-azide-4CR) [1416] and the 1,3-dipolar cycloaddition of azides with (acyl)cyanides [1718]. The Ugi-azide-4CR enables the incorporation of three different diversity-generating sites (Scheme 1), a feature that has been exploited for the construction of libraries of tetrazole-based compounds with potential bioactivity [912 19]. A powerful approach for obtaining hybrid heterocyclic compounds including the tetrazole ring comprises an initial Ugi-azide-4CR followed by a cyclization step, involving some of the reactive functionalities previously installed in the multicomponent process [2026].…”
Section: Introductionmentioning
confidence: 99%